Degos' disease: association with anticardiolipin antibodies and the lupus anticoagulant. Issue 6445 (8th September 1984) - Englert, H J; Hawkes, C H; Boey, M L; Derue, G J; Loizou, S; Harris, E N; Gharavi, A E; Hull, R G; Hughes, G R
Abstract : A woman presented with multiple cerebral thromboses and skin lesions characteristic of Degos' disease. Her serum contained high titres of anticardiolipin antibodies and showed lupus anticoagulant activity, both known to be strong markers of a thrombotic tendency in systemic lupus erythematosus. This finding may have therapeutic implications for this usually fatal disease.